Volatilitas harga pangan pokok di pasar global sebagai dampak pandemi COVID-19 dan resesi ekonomi dunia - Prasmita Dian Wijayati; Dona Laily; Dita Atasa (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Most food commodity prices on the world market increased drastically in late 2006 to mid 2008. The increase in food prices in 2008 was triggered by the global crisis. In 2020, the world is facing a global recession caused by the Covid-19 pandemic. This study aims to examine the impact of the global recession on the prices of several food commodities in the global market. Methods: Analysis of food price volatility in global markets using secondary time series data on monthly staple food prices for the period January 1960 to December 2020 (720 time series). This study analyzes the volatility of staple food prices using the Autoregressive Conditional Heteroscedastic (ARCH) model Generalized Autoregressive Conditional Heteroscedastic (GARCH). Results: The results showed that most food commodity prices had high volatility during the 1973 crisis and 2008 crisis. However, food prices were not too affected by the 2020 global recession. Volatility analysis was conducted to determine the movement of food commodity prices during the crisis and recession. Secondary data obtained from the World Bank's Pink Sheet Data were used in this study. The nature of the data is a monthly time series from January 1960 to December 2020. The volatility analysis is estimated using the ARIMA (Autoregressive Integrated Moving Average) and ARCH-GARCH (Autoregressive Conditional Heteroscedasticity-Generalized Autoregressive Conditional Heteroscedasticity) models. Conclusion: the results of the study indicate that most food commodity prices have high volatility during the 1973 crisis and 2008 crisis. However, food prices are not too affected by the 2020 global recession.